Analisis Sistem Antrian Cafe Ipong Kane Menggunakan Metode Single Channel - Agustin, Sinta Fortuna; Risky, Wiranti Cahya; Ritonga, Eva Indriani; Ritonga, Risa Agustika; Irmayanti, Irmayanti (Indo-MathEdu Intellectuals Journal, 2024)
The purpose of this research is to find out how long it takes customers when experiencing a queue for service at Cafe Ipong Kane using the single channel method. The research methodology used is descriptive observational research by directly observing the queuing system that occurs at the Ipong Kane Café. The results and discussion of this research are the arrival of data and services, and queue calculations. The conclusion of the research that has been carried out is: Single channel model queuing process, from the calculation that the average number of customers waiting in line is around 10 customers within 25 minutes in busy conditions. The average time spent by customers waiting in line is around 9.6 minutes at the longest and 3 minutes at the fastest